Political contestation: Ideology and linguistic realization by 2024 prospective Indonesian presidential candidates - Saragih, Amrin; Khairina, Yuni; Batubara, Khairunnisa Br. (JOALL (Journal of Applied Linguistics and Literature), 2024)
The political statements of prospective presidential candidates in the Republic of Indonesia (RI) in the pre-election period of 2024, in 2023, constitute texts of political contestation (PC) loaded with ideology. This research examines those PC texts. The texts are based on the respective ideologies of each presidential candidate. More specifically, this study investigates the ideologies of the presidential candidates, the linguistic realization used to express those ideologies, and the reasons behind the use of ideology and its linguistic realization. This research employs a qualitative descriptive design. Data collection tools included observation, document analysis, and interviews. The data sources were KP texts from three presidential candidates: Anies Rasyid Baswedan, Ganjar Pranowo, and Prabowo Subianto, obtained from newspapers, television, and social media platforms such as WhatsApp, Twitter, Instagram, and Facebook. The data, in the form of KP texts, were analyzed using the framework of systemic functional linguistic theory (SFL) as developed by Halliday (2014) and other SFL experts. The research findings indicate that, in addition to similarities, the three presidential candidates have differences in leadership ideology, the linguistic realization of that ideology, and the causes or reasons used. The theoretical contribution of this research enriches applied linguistic theories, especially political discourse analysis (PDA), and simultaneously benefits voters in the 2024 election by helping them understand the ideologies of presidential candidates. This understanding can solidify their decision to vote for a specific candidate, thus reducing the social friction that always occurs during elections in Indonesia.